Democratic Citizenship-in-the-Making: Dis/Engagement Profiles of Portuguese Youth - Malafaia, Carla; Ferreira, Pedro D.; Menezes, Isabel (Frontiers in Political Science, 2021)
Coming to terms with the multidimensionsionality of civic and political engagement implies analyzing it in a comprehensive manner: not limited to conventional modes of expression, nor to dichotomic perspectives or observable acts of participation. Studies in this field tend to overlook cognitive and emotional dimensions as types of engagement which, alongside with behavior, constitute citizenship. In this article, we analyze data from the Portuguese sample of the CATCH-EyoU Project’s survey (1,007 young people aged between 14 and 30 years old). The main result is the identification of four distinct profiles according to behavioral, emotional and cognitive forms of engagement: Alienated, Passive, Disengaged and Engaged. These profiles are then examined to assess whether and how they differ in terms of: i) national and European identification, ii) relationships with alternative and traditional media, iii) democratic support, and iv) attitudes towards immigrants and refugees. The relationship between the different profiles and individual socio-demographic variables is also examined. We discuss how different dis/engagement profiles relate with socio-political dimensions and have different consequences both in terms of the political integration of young people and of the political challenges faced by democratic societies.